Writing in the World of Knowledge: Finding one's Voice in School, the University, Career, and Society (2014)
Voice and knowledge are intimately connected. Learning to write gives us voice beyond the range of hearing and takes the adventure of language across time and distance, placing us in social worlds and social projects with people we cannot see and sometimes cannot even imagine. While early childhood literacy education, helps young children express themselves and grow the motive to write out of personal and play relations, as schooling continues those motivating experiences decreases and writing becomes a narrow exercise mostly associated with assessment rather than accomplishing real life interests. Yet writing outside of school is intimately related to participating in society, and skill in writing gives one voice in professional and civic communities. Writing in school needs to be connected to real life uses and intellectual growth of students. Writing should be supported at each level of education, express and share meanings of importance to students, connected with thinking and knowledge is subject areas, connected with reading, and address situations outside of school important to students.